Study of the influence of coal column width on the stress-fracture-displacement evolution law in sequential coal seam mining - Ge Huang; Hexuan Li; Fengwei Dai; Xun Zhang; Wei Gao (Scientific Reports)
Abstract The connectivity of the fissures in the adjacent air section represents a crucial foundation for the deployment of surface gas extraction drill holes in abandoned mines. To elucidate the impact of coal column width on overlying rock movement and fissure development in adjacent mine openings, a theoretical derivation and discrete element simulation approach was employed, utilizing the 8# coal seam in Baode Mine as a case study. The results demonstrate that, as a consequence of mining activities, the stress within the overlying rock layer of the mining area exhibits a distinctive pattern, comprising four distinct phases: concentration-unloading(yielding)-recovery-unloading-concentration. This pattern is observed to intensify with increasing coal column width. The elastic region in the center of the segmental coal column begins to appear as the width of the coal column increases. In addition, the vertical stress curve undergoes a transition from a single-peaked to a double-peaked configuration. Furthermore, the peak of the stress value demonstrates a decline in both velocity and magnitude. The peak stress value demonstrates a decelerating and decreasing trend. The coal column in the section transitions from a completely unstable state to a stable state in a gradual manner. The connectivity between the adjacent mining areas shifts from a completely through state to a gradually closed state. The sinking amount of the coal column in the section decreases from 2.56 m in the unstable state to 0.49 m in the 30 m width and exhibits a tendency towards stability. The findings of the theoretical derivation and simulation analysis suggest that the optimal width for coal columns in the section is approximately 20–25 m.